RELATIONS OF MORPHOLOGICAL CHARACTERISTICS WITH THE FACTOR FOR EXCITATION DURATION OF MOTORIC UNITS OF PRE-SCHOOL CHILDREN - Dragan Martinović; Vladan Pelemiš; Dragan Branković; Vladimir Živanović (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2013)
In a sample of 85 subjects, divided into two sub-samples (55 boys, 30 girls),there were measured 11 anthropometric variables and assessment of one motoric test. The aim of theresearch was to determine the relation of morphological characteristics with the factor for excitation duration of the motoricunits, manifested with the motoric variableEndurance in pull-ups. Based on the results of the linear regression analysis for the boys,it can be concluded that the predictor variable system shows a statistically significant effect on the criterion at the value of the coefficient of multiple correlation R=0.717 which explained 51.3% of the common variance with the criterion. The values of the standardized regression coefficients Beta for the boys indicate that the predictor variable Body height has a statistically significantly positive effect on the criterion, while the variables: Arm length and Shoulder width have a statistically significantly negative effect on the criterion variable. For the girlsthere was not determined statistically significant effect of the predictor system with the criterion.